Controlling the Diffusion of Multidrug-Resistant Organisms in Intensive Care Units - Kernéis, Solen; Lucet, Jean-Christophe (Seminars in Respiratory and Critical Care Medicine, 2019)
The prevalence of multidrug-resistant organisms (MDROs) in intensive care units (ICUs) is increasing worldwide, with very large variations across countries, microorganisms, and settings. Emerging MDR gram-negative bacteria and fungi raise particular concerns that require improved prevention and control strategies. Vertical approaches are mainly based on screening and contact precautions and/or decolonization of MDRO carriers. On the other hand, horizontal strategies are not pathogen-specific and include standard precautions (i.e., hand hygiene), universal decolonization, antimicrobial stewardship, and environmental cleaning. The impacts of the different strategies vary between MDROs and compliance with control measures, and are intermixed in most infection control programs. Based on historical data, hand hygiene remains the cornerstone to prevent transmission of MDROs in ICUs. In the context of high hand hygiene compliance, screening and contact precautions for carriers seem to have a limited additional effect, particularly for MDR gram-negative bacteria. Studies on skin decolonization with chlorhexidine bathing show conflicting results, impairing its widespread adoption. Selective oral and digestive decontaminations have shown positive impact on clinical outcomes in ICUs with low levels of antibiotic resistance, but raised ecological concerns in high-prevalence settings. Antibiotic stewardship programs have been associated with reductions in antimicrobial use, duration of stay, and costs with no negative impact on mortality and should be widely promoted in ICUs. Whatever the strategy, compliance with the recommended measures is of crucial importance and implementation should rely on behavioral approach and change in the institutional and safety culture.
Keywords: multidrug-resistant organisms; intensive care units; infection control